Monitoring Bioaccumulation (in Gills and Muscle Tissues), Hematology, and Genotoxic Alteration in Ctenopharyngodon idella Exposed to Selected Heavy Metals. (15th April 2020) - Shah, Nazish; Khan, Ahsan; Ali, Riaz; Marimuthu, Kasi; Uddin, Muhammad Nazir; Rizwan, Muhammad; Rahman, Khaliq Ur; Alam, Mukhtar; Adnan, Muhammad; Muhammad; Jawad, Shahibzada Muhammad; Hussain, Saddam; et al.
Abstract : Health and environmental problems arising from metals present in the aquatic ecosystem are very well known. The present study investigated toxicological effects of LC15 of metals such as copper, chromium, and lead for 24, 48, 72, and 96 h on hematological indices, RBC nucleus and cell morphology, and gill and muscle tissues of grass carp ( Ctenopharyngodon idella ). Experimental dose concentrations of copper were 1.5, 1.4, 1.2, and 1 mgL −1 . Similarly, dose concentrations of chromium were 25.5, 22.5, 20, and 18 mgL −1 while those of lead were 250, 235, 225, and 216 mgL −1, respectively. Maximum decrease in the concentration of Hb, RBCs, and monocytes was observed against chromium, while maximum increase in the concentration of lymphocytes was reported against lead. Abnormalities such as single and double micronuclei, deformed nucleus, nuclear shift, irregular nucleus, deformed cells, microcyte cells, and vacuolated and swollen cells were observed. Gill tissues absorbed maximum concentration of lead followed by chromium and copper. Muscle tissues also absorbed maximum concentration of lead followed by chromium and copper, respectively. Histological alterations such as epithelial lifting, interlamellar spaces, club gill filaments, gill bridging, curling filaments, swelling and fusion of cells, irregular cells, destruction of epithelial cells, cellular necrosis, and inflammatory cells were observed in gill tissues while inflammation and necrosis of muscle fibers, degeneration of muscle fibers, edema of muscle bundles, zig-zag of muscle fibers, and lesions were observed in muscle tissues of fish exposed with different doses of these heavy metals, indicating the toxicity of metals to aquatic fauna as well as to human being via food chain.